2012
DOI: 10.1159/000339505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Glucose-6-Phosphate Dehydrogenase Deficiency among Jordanians

Abstract: Background/Aims: In Jordan, glucose-6-phosphate dehydrogenase (G6PD) deficiency is a significant health problem, and the incidence was reported to be about 3.6%. The aims of this study are to investigate the most common molecular mutations of the G6PD gene among Jordanians in northern Jordan and to examine the correlation between the genotype and phenotype of this enzyme deficiency. Methods: Seventy-five blood samples were collected from patients attending King Abdullah University Hospital and Princess Rahma T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Moreover, Doss and Alasmar [10] report four variants to be exclusively found in the Arab world, namely p.Asp135Thr, p.Ser179Asn, p.Arg246Leu, and p.Glu307Pro. The variant p.Asp135Thr was observed in Egypt, Palestine, and Jordan [10,22,25], and we report it also here in our cohort with AF of 0.00033074. The variant p.Ser179Asn was reported in Palestine and was also seen in our study (AF = 0.00016537).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, Doss and Alasmar [10] report four variants to be exclusively found in the Arab world, namely p.Asp135Thr, p.Ser179Asn, p.Arg246Leu, and p.Glu307Pro. The variant p.Asp135Thr was observed in Egypt, Palestine, and Jordan [10,22,25], and we report it also here in our cohort with AF of 0.00033074. The variant p.Ser179Asn was reported in Palestine and was also seen in our study (AF = 0.00016537).…”
Section: Discussionsupporting
confidence: 79%
“…Studies conducted in the UAE, Jordan, Iraq, and Oman also reported relatively low prevalence (0.5-8.7%) of G6PD Chatham cases among G6PDD patients [21][22][23][24]. These similarities in G6PD variations observed across different Arab populations reflect the common ancestry and similar genetic background of Arabs.…”
Section: Discussionmentioning
confidence: 89%
“…The enzymopathy, G6PDd is an X-linked disease associated with various degrees of reduced G6PD enzyme activities [ 11 ]. A single amino acid substitution at position A376G converts the genotypic variant B to variant A, and a second amino acid substitution at position G202A result in a change from the A variant into the A- (A376G/G202A) variant [ 12 , 13 ]. The B, A, A- G6PDd variants are the most predominant in sub-Saharan Africa [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the cases were G6PD deficiency (6.7% of neonates examined), which is common in many Eastern Mediterranean nations, including Iraq (25)(26)(27). The incidence of G6PD deficiency in central and southern Iraq has been the subject of some investigations (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%